Synthesis and Characterization of Co-Mo/γ-Alumina Catalyst from local Kaolin clay for Hydrodesulfurization of Iraqi Naphtha - Ahmed zeki, Nada Sadoon; Hussein, Sattar Jalil; Aoyed, Khalifa K.; Ibrahim, Saad Kareem; Mehawee, Ibtissam K. (Journal of Petroleum Research and Studies, 2021)
This work deals with the hydrodesulfurization of three types of naphtha feedstocks; mixed naphtha (WN), heavy naphtha (HN) & light naphtha (LN) with a sulfur content of 1642.1, 1334.9 & 709 ppm respectively, obtained from Missan refinery using prepared Co-Mo/γ-Al2O3 catalyst. The Iraqi white kaolin was used as a starting material for the preparation of γ-Al2O3 support, transferring kaolin to meta-kaolin was studied through calcination at different temperatures and durations, kaolin structure was investigated using X-Ray diffraction techniques. High purity 94.83%. Crystalline γ-Al2O3 with a surface area of 129.91 m2/gm, pore volume 0.9002 cm3/g was synthesized by extraction of Iraqi kaolin with H2SO4 at different acid to clay weight ratios, acid concentrations & leaching time. Ethanol was used as precipitating agent; the resultant gel was dried and calcined at 70OC, 10 hrs & 900 OC, 2 hrs respectively. The effects of different parameters on the average crystallinity and extraction % of synthesized γ-Al2O3 were studied like; acid: clay ratio, sulfuric acid concentration, leaching time, leaching temperature & kaolin conversion to metakaolin. Characterization of prepared γ- Al2O3 & Co-Mo catalyst were achieved by X-ray diffraction, FTIR-spectra, texture properties & BET surface area, BJH N2 adsorption porosity, AFM, SEM, crush strength & XRF tests. Co-Mo/ γ-Al2O3 catalyst with final loading 5.702 wt% and 21.45 wt% of Co and Mo oxides respectively was prepared by impregnation methods. The activity of prepared Co-Mo/γ-Al2O3 catalyst after moulding to be tested for hydrodesulfurization (HDS) of naphtha feedstock W.N, H.N & L.N was performed using a pilot hydrotreating unit at petroleum research & development centre, at different operating conditions. Effects of temperature, LHSV, pressure, time & pore size distribution were studied, the best percentage of sulfur removal is increased with decreasing LHSV to 2 hr-1 as a general trend to be 89.71, 99.72, 99.20 % at 310oC for the whole naphtha, heavy naphtha and light naphtha feedstocks respectively, at 34 bar pressure and 200/200 cm3/cm3 H2/HC ratio.